(untitled) (Global Journal of Human-Social Science, 2023)
This article conducts a debate on professional training in Social Work and the treatment of regional particularities with emphasis on the Amazon In the light of historical and dialectical materialism supported by bibliographical research it proposes a formative process that articulates universality and particularity international and local contexts national and regional demands in the spirit proposed by the Curricular Guidelines constructed by the professional category of social workers in 1996 It is postulated that the generalist formation at the same time that it should form professionals with capacity to act in the plurality of socio-occupational spaces anywhere in the country should also favor responses to regional particularities